Autoimmune pancreatitis type 1 and type 2: A report on two cases - Brčerević, Irina A.; Doder, Radoje; Perišić, Nenad; Petrović, Stanko; Jović, Jasna; Hristović, Dejan; Djordjević, Zoran; Tasić Radić, Olga (Vojnosanitetski pregled, 2017)
Introduction. Autoimmune pancreatitis is a disease associated with autoimmune mechanisms, clinically manifested mostly as obstructive icterus with or with no entire or partial enlargement of the pancreas, histological lymphoplas-mocytic infiltration, fibrosis or granulocytic epithelial lesions with a favourable therapeutic response to the application of corticosteroids. Type 1 autoimmune pancreatitis is a systemic disease befalling the group of IgG4-related diseases in contrast to type 2 which is specific for pancreas disease. Case report. We presented two cases. The first one was a 64-year-old male patient with autoimmune pancreatitis complaining of abdominal pain, weight loss, weakness and exhaustion. Clinical examination showed a rare IgG4 autoimmune pancreatitis. The second one was a 37-year-old male patient complaining of abdominal pain with diarrhea. The diagnosis made revealed the presence of type 2 autoimmune pancreatitis. Following the diagnosis, immunosuppressive therapy was administered to both patients leading to the improvement of their general condition. Conclusion. Autoimmune pancreatitis is a rare disease, sometimes not easy to differ from pancreatic tumor or bile duct tumor with poor prognosis. Thus, early recognition of the disease is very important, since adequate treatment significantly increases the course and the outcomes of the disease.
Keywords: pancreatitis; autoimmune diseases; diagnostic techniques and procedures; diagnosis; differential; drug therapy